Neohydatothrips (Thysanoptera: Thripidae) from China: new species and records, with a key to species - Mirab-Balou, Majid; Tong, Xiao-Li; Yang, Shu-Lan (Zootaxa, 2013)
Three new species of Neohydatothrips (Thripidae: Sericothripinae) are described and illustrated from China: N. concavus sp. n., N. flavicingulus sp. n. and N. luteolipes sp. n.; and two species previously recorded from Taiwan are here reported for mainland China for the first time: N. plynopygus (Karny) and N. tabulifer (Priesner). A key to the 16 Neohydatothrips species recorded from China (including Taiwan) is provided.